Penerapan Pertanian Regeneratif pada Perkebunan Kopi - Evizal, Rusdi; Prasmatiwi, Fembriarti Erry (JURNAL AGROTROPIKA, 2024)
Agronomy not only studies cultivation technology and agricultural production, but also examines the application of agricultural concepts and systems that continue to develop. The rapid and fundamental transformation of the agricultural system called the green revolution is based on the use of high inputs to increase agricultural production. The use of inputs that are not environmentally friendly and the emergence of environmental awareness encourages the transformation of agricultural systems into environmentally friendly agriculture such as ecofarming, organic farming, alternative farming, sustainable agriculture and regenerative agriculture. This article reviews the concepts of sustainable agriculture, degenerative agriculture, regenerative agriculture and the practice of implementing regenerative agriculture on coffee plantations. Degenerative agriculture is an agricultural practice that causes productivity to continue to decline as a result of a decrease in the carrying capacity of the agroecosystem, including soil, plants and other flora, fauna, microbes, climate and society. Sustainable agriculture aims to maintain a desired or improved level of ecosystem function, while regenerative agriculture aims to regenerate, renew, and further improve soil function and ecosystem capabilities in an ever-increasing process. The ecological pillars of regenerative agriculture include (1) soil health, (2) biodiversity, and (3) livestock-crop integration. Regenerative coffee plantation practices include the use of superior clones or varieties, grafting, planting shade trees and mixed crops, and livestock integration.Keywords : Biodiversity, degenerative, integrated, sustainable, regenerative agriculture